Evaluation of music learning during the COVID-19 pandemic in senior high schools - Nugrahhu, Putra Andino (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2023)
The purpose of this study is to see the extent to which the implementation of teaching and learning activities for Cultural Arts subjects, especially in the field of Music Arts at high schools in Palangka Raya, was carried out during the COVID-19 pandemic. This research is evaluation research with a descriptive qualitative approach that uses a discrepancy evaluation model that measures the gaps in the learning process. Data was collected through observation, interview, and documentation techniques and validated using triangulation and source triangulation. The results of the study found that in the evaluation of input, music art learning consisting of curriculum components, lesson implementation plans, teacher qualifications, and learning facilities has run well. However, teacher qualifications and learning facilities need to be reviewed so that they can be adjusted to the standards set by the government. In the evaluation of the music art learning process consisting of teacher performance, student attitudes, class climate, and student learning motivation is in a good category, where the teacher masters the learning material and can manage to learn well, thus creating a class climate, student attitudes, and student learning motivation are in a good category. Music learning outputs are evaluated by the minimum completeness standards set in each school. Music learning programs in schools can still run well, but there needs to be an adjustment of subject teachers' teaching qualifications not to produce outputs that deviate far from the main objectives of art education.